Gnostik bir Hıristiyan : Basilides, hayatı ve görüşleri - Cebiroğlu Erdem, Havva Burcu (My University, 2024)
Bu çalışma, ikinci yüzyıldaki Gnostik Hıristiyanlardan biri olan Basilides (117-161)’in hayatını, öğretilerini ve beslendiği kaynakları incelemektedir. Basilides, hem Gnostik grubun hem de Hıristiyan geleneğin içerisinde ele alınmaktadır. Bu sebeple çalışmamız, öncelikle Gnostisizmin genel öğretileri, ardından Gnostisizm - Hıristiyanlık ilişkisi ve ikinci yüzyılda yaşamış olan Gnostik Hıristiyanlar açıklamaktadır. Çalışmamızın devamında ise kilise babaları ve çağdaş araştırmacılar nazarında Basilides portresi çizilmeye çalışılmaktadır. Bu bağlamda Basilides, ılımlı düalizm anlayışına sahiptir. Buna rağmen Yaratıcı Tanrı’yı Abrasax olarak isimlendirmesi, onu diğer Gnostiklerden ayırt etmektedir.

This study examines the life, teachings, and sources of inspiration of Basilides (117-161), one of the Gnostic Christians of the second century. Basilides is considered within both the Gnostic group and the Christian tradition. Therefore, our study first explains the general teachings of Gnosticism, followed by the relationship between Gnosticism and Christianity, and the Gnostic Christians who lived in the second century. In the continuation of our study, an attempt is made to draw a portrait of Basilides in the eyes of the Church Fathers and contemporary researchers. In this context, Basilides has a moderate dualism understanding. Despite this, his naming of the Creator God as Abrasax distinguishes him from other Gnostics.
A gnostic Christian : Basilides, his life and views
Keywords: Abrasax; Abrasax Basilides; Basilides; Bilinmeyen Tanrı; Christianity; Dinler; dualism; düalizm; Gnosticism; Gnostisizm; Hıristiyanlık; History; Religions; Tarih; Unknown God